2019
DOI: 10.1111/scd.12400
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and burden of caregivers of children and adolescents with disabilities

Abstract: Aims To evaluate the quality of life (QoL) and burden of primary caregivers of children and young adults (PCCYAs) with and without disabilities. Methods A cross‐sectional study was carried out with sample composed of 336 PCCYAs with cerebral palsy (CP; n = 84), Down syndrome (DS; n = 84), autism spectrum disorder (ASD; n = 84), and without disabilities (control group: CG n = 84), matched by gender and age. The burden of caregivers was assessed with the Zarit Burden Interview (ZBI), whereas QoL was assessed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
40
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 26 publications
8
40
1
6
Order By: Relevance
“…Moreover, 58% of caregivers were illiterate. The predominance of women as caregivers corroborates the findings of previous studies [ 22 24 ] which can be explained by the tendency of women to carry out many roles, frequently including domestic work, employment, and caregiving to the family members [ 25 ]. The profiles of the caregivers in the study reveal the cultural tendency and tradition of rural communities in Egypt where participation of illiterate and non-working women in familial caregiving is preferred, especially those who have motherhood experience.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, 58% of caregivers were illiterate. The predominance of women as caregivers corroborates the findings of previous studies [ 22 24 ] which can be explained by the tendency of women to carry out many roles, frequently including domestic work, employment, and caregiving to the family members [ 25 ]. The profiles of the caregivers in the study reveal the cultural tendency and tradition of rural communities in Egypt where participation of illiterate and non-working women in familial caregiving is preferred, especially those who have motherhood experience.…”
Section: Discussionsupporting
confidence: 88%
“…This could be attributed to the fact that better-educated caregivers would have more resources available to manage the care situation and those who had a paid job outside the house are not always available to provide full-time primary care. Caregiver age was associated with the physical burden which was supported by the previous finding which stated that older caregivers experience higher burden and greater impact on their quality of life [22,37]. However, in contrast with Zahid and Ohaeri [38] who found that spouse caregivers reported more burden than other caregivers, we found that being a parent for a disabled person was significantly associated with increased social dimension burden.…”
Section: Determinants Of Caregiver Burdensupporting
confidence: 83%
“…Caring for children with disabilities is a greater burden on older mothers, which has a negative impact on the assessment of their QOL (28). In our study, we did not find a correlation between QOL and age, except that there is a positive and weak correlation (rho = 0.20) of older mothers and the environmental domain.…”
Section: Discussioncontrasting
confidence: 85%
“…Caregivers' potentially lower standard of education prevents them from entering the skilled labor market. Thus, they dedicate themselves exclusively to household chores and taking care of the individual with CP [28]. Emerging concepts of quality of life related to CP are emerging, and in the last five years, a total of 469 articles were found in the literature.…”
Section: Discussionmentioning
confidence: 99%